A Functional Comparison of Homopentameric Nicotinic Acetylcholine Receptors (ACR-16) Receptors From Necator americanus and Ancylostoma ceylanicum - Kaji, Mark D.; Geary, Timothy G.; Beech, Robin N. (Frontiers in Molecular Neuroscience, 2020)
Effective control of hookworm infections in humans and animals relies on using a small group of anthelmintics. Many of these drugs target cholinergic ligand-gated ion channels, yet the direct activity of anthelmintics has only been studied in a subset of these receptors, primarily in the non-parasitic nematode, Caenorhabditis elegans. Here we report the characterization of a homopentameric ionotropic acetylcholine receptor (AChR), ACR-16, from Necator americanus and Ancylostoma ceylanicum, the first known characterization of human hookworm ion channels. We used two-electrode voltage clamp electrophysiology in Xenopus laevis oocytes to determine the pharmacodynamics of cholinergics and anthelmintics on ACR-16 from both species of hookworm. The A. ceylanicum receptor (Ace-ACR-16) was more sensitive to acetylcholine (EC50 = 20.64 ± 0.32 µM) and nicotine (EC50 = 24.37 ± 2.89 µM) than the N. americanus receptor (Nam-ACR-16) (acetylcholine EC50 = 170.1 ± 19.23 µM; nicotine EC50 = 597.9 ± 59.12 µM), at which nicotine was a weak partial agonist (% maximal acetylcholine response = 30.4 ± 7.4%). Both receptors were inhibited by 500 µM levamisole (Ace-ACR-16 = 65.1 ± 14.3% inhibition, Nam-ACR-16 = 79.5 ± 7.7% inhibition), and responded to pyrantel, but only Ace-ACR-16 responded to oxantel. We used in silico homology modelling to investigate potential structural differences that account for the differences in agonist binding and identified a loop E isoleucine 130 of Nam-ACR-16 as possibly playing a role in oxantel insensitivity. These data indicate that key functional differences exist among ACR-16 receptors from closely related species and suggest mechanisms for differential drug sensitivity.